Biodiversity in the Agentinean Rolling Pampa ecoregion: changes caused by agriculture and urbanisation - Faggi, Ana M.; Krellenberg, Kerstin; Castro, Roberto; Arriaga, Mirta; Endlicher, Wilfried (ERDKUNDE, 2006)
The metropolitan area of Buenos Aires is located in the Rolling Pampa, one of the most productive ecoregions of the world (44,000 km2, 33º S – 39º S). This region has undergone deep transformations caused by agricultural, residential, industrial and commercial land-uses. The purpose of this paper is to compare to what extent plant and bird richness are influenced by urban and agricultural uses. To capture the land-use effects a comparison between different sectors was made. Green spaces and farmland, located in areas of contrasting land-use, extending from the La Plata’s river shore to semirural and rural areas, were sampled. Vascular plant richness, floristic composition and bird presence were considered. To compare the different sites biodiversity indexes and Sørensen´s coefficient of similarity were calculated and the percentage of forest, grassland, shrubland, wetland and rivers/streams was estimated. All collected data were correlated using Principal Components Analysis (PCA). In general, the decrease of native plants and bird richness towards the city centre is consistent with the studies of other cities. The results of the present study confirm that the actual cultivation practices are extremely more dangerous for conservation of native land than urban sprawl.